Cleaning ability of chlorhexidine gel and sodium hypochlorite associated or not with EDTA as root canal irrigants: a scanning electron microscopy study - Bruno Carvalho de Vasconcelos; Suyane Maria Luna-Cruz; Gustavo De-Deus; Ivaldo Gomes de Moraes; Claudio Maniglia-Ferreira; Eduardo Diogo Gurgel-Filho (University of São Paulo, 2007)
The aim of this study was to evaluate the cleaning efficacy of 2% chlorhexidine gluconate gel (CHX) compared to 2.5% sodium hypochlorite solution (NaOCl) associated or not with 17% EDTA used as irrigants during the biomechanical preparation. Fifty freshly extracted single-rooted human teeth with complete apex formation were randomly divided into five groups: G1 - sterile saline, G2 - 2.5% NaOCl, G3 - 2% CHX, G4 - 2.5% NaOCl + EDTA and G5 - 2% CHX + EDTA. The specimens of G1 were subdivided into two control groups. The teeth were decoronated and the coronal and middle root thirds were prepared with Gates-Glidden burs, and the apical third was reserved to manual instrumentation. All procedures were performed by a single operator. In all groups, 2 mL of irrigant was delivered between each file change. The teeth were sectioned and prepared for analyses under scanning electron microscopy (SEM). SEM micrographs were graded according to a score scale by two examiners. Data were analyzed statistically by Kruskal-Wallis and Dunn tests at 1% significance level. The best results were obtained in the groups in which the irrigant was used followed by the chelating agent. No statistically significant difference was observed among G4, G5 and the positive control group (p<0.01). The groups G2 and G3 were significantly different from the others, presenting the worst cleaning capacity. In conclusion, the use of the chelating agent is necessary to obtain clean canal walls, with open tubules and no heavy debris. The use of 2% chlorhexidine gluconate gel alone is not able to remove the smear layer.